A Comparative Analysis of Diagnostic Accuracy of Focused Assessment with Sonography for Trauma Performed by Emergency Medicine Resident versus Radiology Residents - Ali, Aniqa; Abidi, Turab Fatima; Ahmed, Adeel (Indus Journal of Bioscience Research, 2025)
Objective: To compare the diagnostic accuracy of focused assessment with sonography for trauma (FAST) performed by emergency medicine (EM) residents versus radiology residents in detecting intra-peritoneal free fluid, using contrast-enhanced computed tomography (CT) of the abdomen as the reference standard. Methods: This cross-sectional diagnostic validation study was conducted over six months (July–December 2024) in the Emergency Department of POF Wah Cantt. A total of 285 adult patients (aged 16–65 years) with blunt abdominal trauma, who were hemodynamically stable, were enrolled through non-probability consecutive sampling. All patients underwent FAST scans performed independently by EM and radiology residents, blinded to each other's findings. The reference test was CT abdomen, reported by a consultant radiologist. Diagnostic accuracy parameters (sensitivity, specificity, positive predictive value [PPV], negative predictive value [NPV], and overall accuracy) were calculated for each group, with subgroup analyses by gender, age, and mechanism of injury. Results: Intra-peritoneal free fluid was confirmed on CT in 43 patients (15.1%). EM residents demonstrated 72.1% sensitivity, 97.1% specificity, 81.6% PPV, 95.1% NPV, and 93.3% accuracy. Radiology residents yielded 74.4% sensitivity, 98.3% specificity, 88.9% PPV, 95.6% NPV, and 95.1% accuracy. Subgroup analyses by gender, age, and injury mechanism revealed consistent performance across all strata. No statistically significant differences were observed between the two groups for any metric (p > 0.05). Conclusion: FAST scans performed by trained EM residents demonstrated diagnostic accuracy comparable to radiology residents, supporting their reliable use in the initial evaluation of blunt abdominal trauma.